DUKUNGAN NORMATIF BAGI PEKERJA PEREMPUAN DENGAN TANGGUNG JAWAB KELUARGA: UU KETENAGAKERJAAN HINGGA UU CIPTA KERJA - Widiastiani, Nindry Sulistya (Faculty of Law, Universitas Tanjungpura, 2026)
This article analyses the existence of normative support for women workers with family responsibilities in Indonesian labour law. The social structure of Indonesian society still views the function of family care as the responsibility of women. Therefore, working women are burdened with dual functions as workers and holders of care responsibilities. Both functions can lead to discrimination in the workplace for women workers. Normative support to protect these female workers is critical to note. The analysis was carried out by examining the regulations in the Manpower Act and the 2023 Job Creation Act. The analysis results show that the Acts contain several articles that provide normative support for women workers with family responsibilities, although they are not yet comprehensive and firm. First, this support is reflected in the regulations that require employers to consider the needs of workers and their families, both in employment relationships and in social security. Second, some provisions prohibit layoffs based on family responsibilities. In addition to these explicit regulations, several provisions can be implicitly interpreted as normative support for women workers with family responsibilities